Fostering In-Depth Learning in Daylighting Design : Insights from two summer schools - Giuliani, Federica; Sokol, Natalia; Gentile, Niko; Lo Verso, Valerio R.M.; Khanie, Mandana Sarey (37th PLEA Conference, Sustainable Architecture and Urban Design: (Re)Thinking Resilience, PLEA 2024, Wroclaw, Poland, 2024-06-26 - 2024-06-28, 2024)
This paper reports on the educational model undertaken in two specialized summer schools in Denmark (2022) and Poland (2023) on daylighting in buildings. As a part of a European educational initiative, these schools aimed to deepen participants' understanding of the impact of daylight on building design. The programme, a collaborative effort between universities, companies, associations, professionals, and students, integrated an online platform for theoretical knowledge with practical summer schools. The paper presents the objectives and results of the summer schools, the project-based learning outcomes, topics and the structure of the teaching activities. The participants' positive responses highlight the summer schools' success and suggest future improvements.
Publisher Copyright: © Copyright by Fundacja PLEA 2024 Conference, Wrocław 2024.
Keywords: Daylighting design; Educational model; Multidisciplinary education; Participant feedback; Project-based learning